Oxaliplatin-Induced Pulmonary Toxicity in Gastrointestinal Malignancies: Two Case Reports and Review of the Literature. (10th May 2015) - Moskovitz, Mor; Wollner, Mira; Haim, Nissim
Abstract : Oxaliplatin is a common chemotherapy drug, used mainly for colon and gastric cancer. Most common side effects are peripheral sensory neuropathy, hematological toxicity, and allergic reactions. A less common side effect is pulmonary toxicity, characterized mainly by interstitial pneumonitis. The incidence of this side effect is unknown, but the toxicity can be fatal. Twenty-six cases of pulmonary toxicity have been described in the literature, seven in the setting of adjuvant treatment. We describe two fatal cases of pulmonary injury related to oxaliplatin and a review of the literature.